Comparison of the macrofilaricidal efficacy of oxfendazole and its isomers against the rodent filaria Litomosoides sigmodontis - Risch, Frederic; Koschel, Marianne; Lenz, Benjamin; Specht, Sabine; Hoerauf, Achim; Hübner, Marc P.; Scandale, Ivan (Frontiers in Tropical Diseases, 2022)
Oxfendazole is one of the lead macrofilaricidal candidates for the treatment of onchocerciasis and lymphatic filariasis. Originally, oxfendazole was developed for the veterinary market, where it is mainly used to treat intestinal helminth infections. In humans, oxfendazole was proven to be safe in multiple ascending dose studies. Furthermore, previous experimental studies demonstrated that the benzimidazoles class is active in animals and humans against filarial nematodes. In the present study, we have compared the efficacy of oxfendazole isomers with the commercially available racemic mixture Dolthene against the rodent filaria Litomosoides sigmodontis in female BALB/c mice. Treatment with either the isomers or Dolthene led to a reduction of the adult worm burden by 94-98% following the ten-day treatment and by 72% (oxfendazole (-)), 85% (oxfendazole (+)) and 91% (Dolthene) following the five-day treatment. No statistically significant differences in the macrofilaricidal efficacy against L. sigmodontis were observed for both isomers and Dolthene. Metabolites of oxfendazole are fenbendazole and fenbendazole sulfone. Two hours after treatment with Dolthene and both oxfendazole isomers, fenbendazole sulfone, but rarely fenbendazole, was detected. The oxfendazole (-) isomer was metabolised at the highest rate to fenbendazole sulfone. Furthermore, oxfendazole isomers have a comparable pharmacokinetic profile in dogs. In conclusion, our data does not point at the development of a single isomer for future use in humans.